The Antimicrobial Stewardship Approach to Combating Clostridium Difficile - Eric Wenzler; Surafel G. Mulugeta; Larry H. Danziger (Antibiotics, 2015)
Clostridium difficile remains a major public health threat and continues to contribute to excess morbidity, mortality and healthcare costs. Antimicrobial stewardship programs have demonstrated success in combating C. difficile, primarily through antibiotic restrictive strategies. As the incidence and prevalence of C. difficile associate disease continues to increase both in the hospital and community setting, additional stewardship approaches are needed. This manuscript reviews stewardship interventions that have been successful against C. difficile associated disease and proposes future tactics that antimicrobial stewardship programs may employ to develop a more global approach to combat this difficult pathogen.